2013
DOI: 10.1007/s11434-012-5661-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term climatic impacts of afforestation in the East Asian monsoon region

Abstract: The influence of changes in vegetation cover on short-term climate over the East Asian monsoon region is simulated using the Community Climate System Model Version 3.5. The results show the annual mean surface air temperature significantly decreases by 0.93°C in response to afforestation over the East Asian monsoon region. Also, surface air temperature decreases by 1.46 and 0.40°C in summer and winter, respectively. The cooling is caused by enhanced evapotranspiration (ET) produced by increased forest cover. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Large-scale afforestation in the pan-tropical and western European regions would increase precipitation [27,28]. In East Asia, Madi et al used the CCSM (Community Climate System Model) to study and find that with the increasing of forest coverage in east Asian monsoon areas, the annual average precipitation increased, and the precipitation in April increased the most significantly, reaching 7% [29]. Precipitation and the variations of land cover land use type considered the influence of each other, and most of the simulations showed that the farmland and pasture expanded at the expense of the trees and shrubs, and precipitation and surface temperature rise in the resulting Sahel region fell [30].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale afforestation in the pan-tropical and western European regions would increase precipitation [27,28]. In East Asia, Madi et al used the CCSM (Community Climate System Model) to study and find that with the increasing of forest coverage in east Asian monsoon areas, the annual average precipitation increased, and the precipitation in April increased the most significantly, reaching 7% [29]. Precipitation and the variations of land cover land use type considered the influence of each other, and most of the simulations showed that the farmland and pasture expanded at the expense of the trees and shrubs, and precipitation and surface temperature rise in the resulting Sahel region fell [30].…”
Section: Introductionmentioning
confidence: 99%
“…The Shiwan Dashan National Forest Park and the Daming Mountain National Natural Reserve are located in this research area. Some research has already highlighted that the significant role of precipitation may increase or decrease alongside afforestation 4 5 6 or deforestation.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…This, in turn, changes local precipitation through atmospheric circulation on a small to medium scale. Previous research showed that precipitation can increase456 with the growth of forest coverage. Different vegetation types also have distinct impacts on the surrounding climate7.…”
mentioning
confidence: 98%